Seroprevalence of anti-SARS-CoV-2 IgM and IgG and COVID-19 vaccine uptake in healthy volunteers in Nairobi, Kenya: a cross-sectional study - Otindo, Agnes Muhonja; Ndombi, Eric M.; Theuri, Martin; Muturi, Margaret; Thamaini, Peris; Ogutu, James; Onsongo, Lister; Madete, June K.; Ofula, Victor; Gitau, Samuel; Mwangi, Gladys; Okemo, Paul (Frontiers in Virology, 2024)
IntroductionSeroprevalence of anti-severe acute respiratory syndrome coronavirus 2 (anti-SARS-CoV-2) antibodies in the postvaccination period in Kenya remains to be elucidated. This study aimed to determine the seroprevalence of anti-SARS-CoV-2 IgM and IgG and evaluate Covid-19 vaccination uptake in a university setting in Nairobi.MethodsThis cross-sectional study assayed serum anti-SARS-CoV-2 IgM and IgG levels using enzyme-linked immunosorbent assays. A structured questionnaire was used to determine vaccine uptake, vaccine hesitancy and reasons for hesitancy.ResultsA total of 189 participants were enrolled (median age, 21 years; female, 50.8%). The seroprevalence of anti-SARS-CoV-2 was 12.7% for IgM and 87.8% for IgG. Anti-SARS-CoV-2 IgG titers were higher among the vaccinated vs. non-vaccinated individuals (p < 0.001, U = 2817.5), females vs. males (p = 0.024, U = 3616), and those vaccinated ≤ 6 months before the study vs. those vaccinated >1 year earlier (p = 0.002, H = 12.359). The vaccination hesitancy rate was 43.4% and the underlying reasons included mistrust (22.4%), health concerns (19.7%), and lack of information (18.4%).DiscussionThe high seroprevalence of anti-SARS-CoV-2 IgG is an indication of high exposure to SARS-CoV-2 either through natural infection or through vaccination. The high vaccine hesitancy noted necessitates community engagement, and public education to dispel myths and misinformation prior to roll out of new vaccines and other health interventions.